Cortinarius pseudocisticola (Agaricales, Cortinariaceae), a new species in section Calochroi from Europe - Dovana, Francesco; Boccardo, Fabrizio; Borovička, Jan; Vizzini, Alfredo; Saar, Günter; Albert, László; Mikšík, Michal; Dima, Bálint (Phytotaxa, 2021)
A new species of Cortinarius sect. Calochroi, C. pseudocisticola from European deciduous forests, is described on the basis of morphological and genetic features. Several collections of the species from the Czech Republic, Germany, Hungary and Italy were studied. Illustrations of fresh basidiomes in situ and of the main macro- and micromorphological features are provided. Its morphological characters are compared to those of the molecularly closest related and most similar species.